Prove that #lim_(x rarr2) ( 2^x-4 ) / (x-2) =ln16#?

Answer 1

# f'(2) = ln 16 \ \ \ # QED

Given the context of the question, we can see that this limit is the derivative of the function #f(x)=2^x# when #x=2#, Using the limit definition of the derivative, we calculate this using:
# f'(2) = lim_(x rarr2) ( f(x)-f(2) ) / (x-2) # # \ \ \ \ \ \ \ \ = lim_(x rarr2) ( 2^x-2^2 ) / (x-2) # # \ \ \ \ \ \ \ \ = lim_(x rarr2) ( 2^x-4 ) / (x-2) #

Let us perform a substitution, where:

# u = x-2 #
Clearly as #x rarr 2 => u rarr 0#, and so we can rewrite the limits as:
# f'(2) = lim_(u rarr 0) ( 2^(u+2)-4 ) / (u) # # \ \ \ \ \ \ \ \ = lim_(u rarr 0) ( 2^2 2^u-4 ) / (u) # # \ \ \ \ \ \ \ \ = 4 \ lim_(u rarr 0) ( 2^u-1 ) / (u) #

Now we require some additional knowledge of logarithms and specific calculus limits, which provides the value of the limit

# lim_(u rarr 0) ( a^u-1 ) / (u) = ln a#
Where #ln# denotes the Natural Logarithm, ie a logarithm to base #e#, where #e# is Euler's Number. Using this result we get:
# f'(2) = 4 \ ln2 # # \ \ \ \ \ \ \ \ = ln 2^4 # # \ \ \ \ \ \ \ \ = ln 16 \ \ \ # QED
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To prove ( \lim_{x \to 2} \frac{2^x - 4}{x - 2} = \ln 16 ), we can use L'Hôpital's Rule or evaluate the limit directly by recognizing the form ( \frac{0}{0} ) as ( x ) approaches 2.

Using L'Hôpital's Rule, we take the derivative of the numerator and denominator with respect to ( x ), then evaluate the limit again:

[ \lim_{x \to 2} \frac{2^x - 4}{x - 2} = \lim_{x \to 2} \frac{\frac{d}{dx}(2^x - 4)}{\frac{d}{dx}(x - 2)} ]

[ = \lim_{x \to 2} \frac{\ln(2) \cdot 2^x}{1} = \ln(2) \cdot 2^2 = \ln(4) = \ln(16) ]

Alternatively, we can factor ( 2^x - 4 ) as ( 2^2(2^{x - 2} - 1) ):

[ \lim_{x \to 2} \frac{2^x - 4}{x - 2} = \lim_{x \to 2} \frac{2^2(2^{x - 2} - 1)}{x - 2} = 2^2 \lim_{x \to 2} \frac{2^{x - 2} - 1}{x - 2} ]

Recognizing the form ( \frac{0}{0} ), we can evaluate the limit directly:

[ = 2^2 \cdot \ln(2) = \ln(4) = \ln(16) ]

Therefore, ( \lim_{x \to 2} \frac{2^x - 4}{x - 2} = \ln 16 ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7